Phakopsora pachyrhizi is the major pathogen associated with soybean rust in Colombia (2021)
Soybean crops grown in the plains of eastern Colombia have been affected by the incidence of rust. This disease, still officially regarded as American soybean rust (caused by Phakopsora meibomiae) by the Colombian Department of Agriculture (ICA), causes serious damage to soybean growing areas. Symptoms of rust, such as reddish-brown lesions, have been observed since 2004 in the upper half of plants during vegetative stages. In 2005 and 2018, infected leaf tissues and uredinospores were collected from an experimental area and from commercial soybean fields. Once morphological identification and Koch’s postulates confirmed the presence of Phakopsora spp., molecular characterization was performed to identify the pathogen associated with the disease to species level. This was based on standard procedures using internal transcribed spacer (ITS) regions of rDNA and PCR amplification with specific primers for Phakopsora meibomiae and P. pachyrhizi. The obtained sequences were BLASTed against GenBank/ NCBI data bank. Results indicated that P. pachyrhizi Sydow is in fact the causative agent of soybean rust in Colombia, considering the samples collected in 2005 and 2018. The ITS-rDNA sequences of P. pachyrhizi were deposited at GenBank under the accession numbers MK933723 to MK933731. This finding was reported to ICA, so that they could officially update the phytosanitary status of this soybean pathogen in Colombia.